PEMENUHAN EKSPEKTASI, PERBAIKAN DAN PERUBAHAN, MENCIPTAKAN KEKUATAN, KELAYAKAN USAHA, DAN PENGUASAAN TEKNOLOGI DALAM MENOPANG PENGEMBANGAN USAHA MIKRO DI JAWA TIMUR - artaya, i putu -; Kamisutara, Made (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2025)
The purpose of this research is to assist micro-entrepreneurs in eight cities: Sidoarjo, Gresik, Tuban, Mojokerto, Pasuruan, Lumajang, Jember, and Situbondo. The main objective is to support their business development to make them more competitive and expand their market. Five variables were used for the business development process: meeting expectations, improving and changing, creating strengths, business feasibility, and technological mastery. The research location was a micro-enterprise center in East Java, a long-established micro-enterprise center that sells various types of products. The population and sample size were the same, i.e. 84 entrepreneurs, and were classified as saturated samples. The data collection method used research instruments distributed using Microsoft Forms via WhatsApp. The analysis method used multiple linear regression analysis, with the aim of estimating the regression equation. Hypothesis testing prioritized partial hypothesis testing of the five variables used. The test results showed that three variables had a significant influence: meeting expectations, improving and changing, creating strengths, and two independent variables, i.e. business feasibility, and technological mastery, turned out to be insignificant. Based on the test results, business actors must focus on two areas, i.e. business feasibility and technology implementation. Insignificant means that these two variables are not optimal and have not provided satisfactory results for these micro business actors.